Eksplorasi Konsep Sains dalam Produksi Roti Kenari: Pendekatan Multidisiplin untuk Memahami Budaya dan Konteks Sains - Taher, Tamrin; Ali, Lalu Usman (International Journal of Science, Technology and Applications, 2024)
The process of making walnut bread is a dynamic process where the flour components and other ingredient mixtures undergo physicochemical changes. The aim of this study is to explore scientific concepts both at the preparation, process and product stages in the form of walnut bread. Analysis was also carried out to determine the integration of sin concepts according to Fogarty's view. This study uses descriptive qualitative methods. Data collection techniques through libraries. The results of the analysis show that the process of making walnut bread involves scientific concepts including physics, chemistry and biology. These concepts include colloids, collisions, fermentation, temperature and heat, reaction rates, Maillard reactions and caramelization and spoilage processes in food..